2019
DOI: 10.1002/mma.6032
|View full text |Cite
|
Sign up to set email alerts
|

Hopf bifurcation analysis in a multiple delayed innovation diffusion model with Holling II functional response

Abstract: A nonlinear mathematical model with Holling II functional response describing the dynamics of nonadopter and adopters population in a stage structured innovation diffusion model, which incorporates the evaluation stage (multiple delays), is proposed. Firstly, we study the stability and the existence of periodic solutions via Hopf bifurcation with respect to both delays at the positive equilibrium by analyzing the distribution of the roots of the corresponding exponential characteristic equation obtained throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In this section, we use the method in [21] to discuss the system's positivity and uniform boundedness. en, the solutions u(t) and v(t) of system (6) are nonnegative, for all t > 0.…”
Section: Stability and Hopf Bifurcationmentioning
confidence: 99%
“…In this section, we use the method in [21] to discuss the system's positivity and uniform boundedness. en, the solutions u(t) and v(t) of system (6) are nonnegative, for all t > 0.…”
Section: Stability and Hopf Bifurcationmentioning
confidence: 99%
“…That is, reinfection likely occurs [6,7]. It is shown that time delay is of great significance in many biological modelling, and its change may affect the dynamic behavior of the system [4][5][6][9][10][11][12][13][14][15][16][17][18][19], such as stability, uniqueness, and oscillation of solution. So, it is instructive to consider a mathematical model with time delays to research the influence of immunity on disease control of malaria transmission.…”
Section: Introductionmentioning
confidence: 99%